PENGENALAN ETNOBOTANI TUMBUHAN OBAT PADA MASYARAKAT DESA SANUR KAJA - Dharmadewi, A.A. Istri Mirah; Suryatini, Kadek Yuniari; Wiadnyana, I Gusti Agung Gede (Jurusan Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Timor, 2024)
This study was conducted on the people of Sanur Kaja Village who still use medicinal plants as treatment. The purpose of this study was to obtain data on the types of plants and to find out how the people of Sanur Kaja Village process them as traditional medicinal plants and to find out how the people of Sanur Kaja Village process them as traditional medicine. The research used in this study was the Random Sampling method, in determining respondents using the Slovin formula. In this study, interviews were conducted with 50 people in Sanur Kaja Village. The data taken included: types of plants used as medicine, parts used and how to use them. Data analysis in this study was in the form of qualitative descriptive analysis. Based on the results of the study, 15 types of plants were found that could be used as medicine with the dominant plants used as medicine being turmeric, betel, ginger, temulawak and mengkudu. The parts of the plant used as medicine by the people of Sanur Kaja Village are leaves, stems, fruits, rhizomes and tubers. The way of processing plants used as medicine by the people of Sanur Kaja Village is by boiling, burning, chewing, crushing, grating, pounding, heating. Ethnobotany studies in Sanur Kaja Village are the first step to provide traditional knowledge to the village community about plants that are useful as medicine so that they can be passed on to the next generation.